Penerapan Model Pembelajaran Kooperatif NHT Berbantuan Teka-Teki Silang Untuk Meningkatkan Penguasaan Hiragana dan Katakana - Ni Made Dwi Nita Arsani; Desak Made Sri Mardani; Irvina Restu Handayani (STKIP AGAMA HINDU SINGARAJA, 2023)
This study aims to improve the mastery of hiragana and katakana letters, as well as students' responses to the application of the numbered heads together (NHT) cooperative learning model assisted by crossword media. This type of research is a class action research (CAR) with two cycles. This research was conducted at SMA Negeri 4 Singaraja. The subjects of this study were students of class XI BB 1 with a total of 26 students. Data collection methods used are observation methods, test methods, and questionnaire methods. This study shows that the application of the numbered heads together (NHT) cooperative learning model assisted by crosswords media can improve students' mastery of hiragana and katakana letters. This increase can be seen from the percentage of completeness of students' scores before the action until cycle II. On the results of the pre-test the percentage of students' completeness was 19.23%. In cycle I, the percentage of student completeness was 84.61%. Whereas in cycle II, the percentage of student completeness increased to 100%. Student responses to the application of the numbered heads together (NHT) cooperative learning model assisted by crossword media were positive. In cycle I, the average student response was 33.61. In cycle II the average student response was 35.80. The conclusion of this study is that the application of the numbered heads together (NHT) cooperative learning model assisted by crossword puzzles can improve students' mastery of hiragana and katakana letters with a positive response.